Higgs boson production at Linear Colliders from a generic 2HDM: the role of triple Higgs self-interactions - López-Val, David; Solà Peracaula, Joan (Arxiv, 2012)
We review selected results for Higgs boson production at Linear Colliders in the framework of the general Two-Higgs-Doublet Model (2HDM). We concentrate on the analysis of i) the pairwise production of neutral Higgs bosons (hA,HA); and ii) the neutral Higgs boson-strahlung modes (hZ, HZ). We identify sizable production rates, in the range of 10-100 fb for center-of-mass energies of 0.5 TeV, alongside with large quantum effects (up to 50 %), which we can fundamentally track down to the enhancement power of the triple-Higgs self-interactions. This constitutes a telltale signature of the 2HDM, with no counterpart in e.g. the Minimal Supersymmetric Standard Model (MSSM). We compare these results with several complementary double and triple Higgs-boson production mechanisms at order O(α^3_{ew})-O(α^4_{ew} and spotlight a characteristic phenomenological profile which could eventually be highly distinctive of a non-supersymmetric two-Higgs-doublet structure.